A5.30 Systemic Inflammation and B-Cells in Rheumatoid Arthritis. (25th February 2013) - Blits, M; Vosslamber, S; Lubbers, J; Ridder, S de; Oostlander, AE; Wolbink, GJ; Schaardenburg, D van; Nurmohamed, MT; Pegtel, DM; Verweij, CL
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is heterogeneous in clinical symptoms, clinical parameters, pathogenesis and gene expression levels. Previously, we demonstrated variation in B-cell related gene expression between RA patients. The aim was to explore the relation of B-cell related gene expression to clinical parameters of disease severity in early arthritis (EA) and established RA (esRA). Methods: B-cell related gene expression (B-cell score) was determined in peripheral blood cells of 26 EA and 180 esRA patients, using multiplex real-time PCR. For the EA cohort, B-cell counts were also measured using flow cytometry. The esRA cohort was (randomly) divided into test and validation group of each 90 RA patients, with a mean DAS28 of 5.0 and 5.2, respectively. Associations were assessed between B-cell scores and the clinical disease parameters DAS28, CRP, RF, anti-CCP, nodules and erosions in all cohorts and B-cell counts only in EA cohort. Statistical testing was executed according to a bootstrap method which randomises the esRA group a 1000 times into two equally sized groups. Results: We demonstrated that the B-cell score reflected the peripheral blood B-cell count (p < 0.0001, r = 0.7463). In EA, the B-cell score revealed a significant negative correlation with CRP levels (p = 0.0175; r = –0.4618). In the esRA group we also observed a negative correlation between the B-cell score and CRP levels (p = 0.0006, r = –0.3542; p = 0.0096 after Benjamini-Hochberg multiple testing correction). This result was confirmed in the independent validation group (p = 0.0356; r = –0.2218). Additionally, we performed a randomisation with the bootstrap method, which showed the same significant correlations in almost all cases. However, no correlations were found between B-cell score and DAS28, RF, anti-CCP, nodules or erosions. Conclusions: The B-cell score reflects the B-cell count in RA and a low B-cell count is associated with an increased marker of systemic inflammation in RA.